(untitled) (Bulletin KNOB, 2009)
The Carthusian monastery in Roermond, founded in 1376 and closed in 1783, is the best preserved Carthusian monastery in the Netherlands, in spite of two fires, looting, closure and partial demolition that took their toll. This article concentrates on decorations in the stucco work applied in the 18th century, at a time when this part of the Netherlands was under Austrian sovereign rule. The stucco ceiling in the refectory dates from 1748 and is divided into four richly decorated sections by (older) secondary beams. Central are the initials MAR, IHS, IOHS, referring to Mary, Jesus and John the Baptist. This combination dates back to an older tradition under the influence of Bernardino of Siena, but there are also more recent examples of it, applied indoors by Roman Catholics. On the ceiling in the refectory of the Roermond Carthusian monastery there is an abundance of Christian symbolism in the form of stylized animals and plants. Centrally above the eastern entrance there is a dove (the Holy Spirit) with halo in the first section, provided with the Maria monogram, followed by the section with IHS, the Christ monogram. In the third section John the Baptist follows in monogram and with his as well as his ‘opponent’ Salomé’s face. In the fourth section the year 1748 was applied in leaf figures and above the western door there is a pelican feeding its young with the blood from its own breast. This is a reference to Christ’s sacrifice of the cross. The monastic church has stucco vaults dating from 1759. After the closure of the Roermond monastery, the main altar made by F.X. Bader in 1769 was moved to the abbey of Thorn, also situated in the Netherlands province of Limburg. The tabernacle of the main altar is crowned by a pelican, making a connection between the body of Christ and his death on the cross, the Last Supper, and the celebration of the Eucharist, as also depicted symbolically in the fourth section of the ceiling in the refectory.